Children's pragmatic comprehensive: A relevance-theoretic analysis of Mandarin-speaking children - Lina, Tao (Animo Repository, 2010)
This study examined 3-7-year-old Mandarin-speaking children's ability to use context and compensatory comprehension strategies employed by these children when they are in the absence of full comprehension. Fifty (50) children (ten children for each age) were involved in the study. All participants are monolingual Mandarin-speaking belonging to varying class families. All the children are the only child in their families because of Chinas one-child policy. Each child was interviewed individually and 15 questions (consisted of the three types of questions) were asked to explore children's pragmatic comprehension ability. After recording the interview, children's answer were transcribed and coded for the following variables: (1) the frequency of correct answer to reference assignment, enrichment and implicature questions; (2) the types of incorrect answers to the three types of questions; (3) the frequency of incorrect answers to the three question types. One-way unrelated ANOVA was adopted for statistical treatment. The following results was shown: (1) there was an evident developmental pattern for children aged 3 to 7, indicating that an increasing ability to use complex contextual information was related to age; (2) seven types of compensatory strategies were used by children when they were in the absence of full comprehension: World knowledge and own experience, Given information, Don't know, Irrelevant, Keep silence, Tautology and Turn-taking; (3) with age increase, children used less unsophisticated strategies and more sophisticated strategies, albeit not appropriate.